Pengaruh Komposisi Cangkang Telur Sebagai Energizer Pada Proses Pack Carburizing Baja AISI 1018 Terhadap Peningkatan Sifat Mekanik - Azmy, Ilham; Masruri, Deden; Shalahudin, Andhika Jalu (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2023)
AISI 1018 steel is classified as low-carbon steel which is widely utilized for mechanical components, construction, and pipes owing to its high strength and ductility. However, this steel has a limitation to less several mechanical properties viz. hardness and wear resistance. In this work, the pack carburizing process by using different composition of activated carbon and eggshell as energizer have been attempted to strengthen mechanical properties of AISI 1018 steel. The AISI 1018 steel specimens were heated in the furnace at 850 oC and holding time 3 hours, which subsequently rapid cooling process by sink into the water. The composition variations of pack carburizing process mainly contain 95% activated carbon - 5% eggshell, 85% activated carbon - 15% eggshell, and 75% activated carbon - 25% eggshell. Afterwards, it has clearly depicted that pack carburized AISI 1018 using 95% activated carbon - 5% eggshell as energizer possess intriguing microstructure transformation which influence to mechanical properties improvement such as high hardness value (394,2 HV) and good wear resistance (0,074 mm3/minute). Therefore, pack carburized AISI 1018 using 95% activated carbon - 5% eggshell as energizer gives a significant development to enhance AISI 1018 mechanical properties for long-life usage.